KIR2DL3 and KIR2DL1 show similar impact on licensing of human NK cells. Issue 1 (2nd November 2015) - Sim, Malcolm J. W.; Stowell, Janet; Sergeant, Ruhena; Altmann, Daniel M.; Long, Eric O.; Boyton, Rosemary J.
Abstract : Killer cell immunoglobulin‐like receptor/HLA class I (KIR/HLA‐I) combinations are associated with disease risk, implicating functional roles for NK cells (NKCs) or KIR + T cells. KIR/HLA‐I interactions can act through inhibition of NKC activation by target cells and NKC licensing for greater intrinsic responsiveness. We compared licensing conferred by the weaker, HLA‐C group 1/KIR2DL3, and the stronger, HLA‐C group 2/KIR2DL1, inhibitory combinations. The "rheostat model" predicts weaker licensing by HLA‐C1/KIR2DL3 interactions than HLA‐C2/KIR2DL1. We analyzed degranulation in NKC subsets expressing single and multiple receptors for HLA‐I. NKG2A had the strongest licensing impact, while KIR2DL3, KIR2DL1, and KIR3DL1 were weaker, and not significantly different to each other. Presence of one or two matched HLA‐C allotypes did not alter licensing of KIR2DL3 + and KIR2DL1 + NKC. Coexpression of activating KIR2DS1 disarmed KIR2DL3 + and KIR2DL1 + NKC to a similar extent. KIR3DL1 and NKG2A combined for more enhanced licensing of double‐positive NKC than the combination of KIR2DL3 and KIR2DL1. Thus, KIR2DL3 and KIR2DL1 have similar capacity to license NKC, suggesting that inhibitory signal strength and amount of available HLA‐C ligands do not correlate with NKC licensing. Altogether, our results show that the basis for disease associations of HLA‐C and KIR2DL likely encompasses factors other than licensing.